Institutional and Legal Control of Gas Flaring in the Niger Delta Region of Nigeria - Ijaiya, Hakeem; La-Kadri, Mutiat Abdulsalam; Jimoh, Maryam Bayero (Faculty of Law, Universitas Brawijaya, 2018)
The emission of â€œgreenhouse gasesâ€ into the air has adverse effects on the environment. This study examines the effects of gas flaring on the Niger Delta Region of Nigeria. It analyses the institutional and legal framework that prevents gas flaring in the region. The paper appraises the effectiveness of the existing laws on gas flaring with a view to suggest viable means of reviewing the laws. The study found that continuous flaring of gas in the region over the last forty years has adversely bring about health challenges, climate change and loss of income in the region in particular and Nigeria as a whole. The study also found that the laws are too many and ineffective and that the regulatory institutions lack the necessary authority for their enforcement. The paper concludes that basic human rights can only be enjoyed in a pollution free environment. The paper therefore recommends amongst other that applicable laws should be amended, harmonized and domesticated where necessary.The study relies on primary and secondary sources of information like Constitution, Constitutional documents, Statutes, Judicial precedents, International Conventions and Treaties, Books, Journals and Internet materials. The information obtained through these sources was subjected to content analysis.